Usability Test on the System Determination Decision Support ReleaseProduct Towards Contribution Level Decision Maker - Erna Daniati; Sucipto Sucipto; Anita Sari Wardani; Akmal Hisyam Pradhana (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
The core problem addressed in this research is the usability challenges of a decision support system for determining product release, which can hinder decision-makers’ effectiveness and user satisfaction. The purpose of this research is to evaluate the usability of the system and assess its impact on the effectiveness of decision-makers in determining product releases. The method used is a usability test involving direct user interaction with the system, where decision-makers performed predefined tasks. Usability metrics, including task completion time, error rate, and user satisfaction levels, were collected and analyzed to evaluate system performance. The result of this study is that the system facilitates efficient decision-making to a moderate extent. However, specific usability issues, such as navigation complexity and information overload, were identified, which reduced some users’ ability to operate the system seamlessly. Improvements in navigation and information presentation significantly enhanced user experience and decision-making quality. The research concludes that enhancing the usability of decision support systems is essential for maximizing their contribution to decision-making processes. Addressing specific challenges, such as simplifying navigation and optimizing information presentation, can substantially improve decision-maker satisfaction and the overall utility of the system. This study emphasizes the importance of usability-focused design in facilitating effective organizational decision-making.